(3GdOQQ GdefXe aj GdCSe GdCYXes - (3CHh SGde eMeO Hf WdMI ceGd GdOjfs
(3ChdgG (B:s
(3GdMeO ddg GdPi GWdY ef ELJHGg ef YHGOg GdGHQGQ Ydi NHGjG GdGSQGQ hHYO aEfg deG QRbfi Gddg JYGdi ehGNGg YHO UGdM Jbi heUGaGg Ndjd aGdM fbi GfRdJgG ef bdHi s
(3BNQgG (B:s
(3hdGJUQa QLGi Yf hLgc NGjHkG hCf JLYd MSf Xfi ai Yahc cGPHkG haGQbJ Scfi jG CQMe GdQGMejf gPG GNQg hGddg GYde hGdMeO ddg QH GdYGdejf Cejf s
(3HgG fXGe GdJYbjHIs
(3cJHJ Yf fSNI GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
(3NOGHNT HJfg (B(3083) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs